Facilitators, barriers, and guidance to successful implementation of multidisciplinary transitional care interventions: A qualitative systematic review using the consolidated framework for implementation research - Romain Collet; Juul van Grootel; Marike van der Leeden; Marike van der Schaaf; Johanna van Dongen; Suzanne Wiertsema; Edwin Geleijn; Mel Major; Raymond Ostelo (International Journal of Nursing Studies Advances)
Background: Multidisciplinary transitional care interventions aim to improve the coordination and continuity of healthcare during hospitalization and after discharge for patients with complex care needs related to physical, nutritional, or psychosocial status. Implementing such interventions is complex as they involve many stakeholders across multiple settings. Numerous studies have evaluated patients’, family members’, and healthcare professionals’ experiences with multidisciplinary transitional care interventions, which can provide insight into facilitators and barriers to their implementation. Objective: To provide an overview of facilitators and barriers to implementing multidisciplinary transitional care interventions, which could be considered before developing implementation strategies. Design: A qualitative systematic review using the Consolidated Framework for Implementation Research. Setting(s): Hospitals and primary care Participants: Adult patients admitted to a hospital, regardless of their diagnosis, as well as their family members and hospital and primary care healthcare professionals Methods: Embase, CINAHL, and Medline were searched for qualitative studies evaluating multidisciplinary transitional care interventions through patients', family members', and healthcare professionals' experiences and views from inception until June 2024. The methodological rigor was assessed with the Critical Appraisal Skills Program. We identified facilitators and barriers to the successful implementation of multidisciplinary transitional care interventions with the Consolidated Framework for Implementation Research. Facilitators and barriers were categorized into pre- or post-discharge or general factors. Results: Twelve studies were included and appraised. We identified 79 factors, mostly linked to three domains of the Consolidated Framework for Implementation Research: Innovation, Inner setting, and Individuals involved. Facilitators included ''comprehensive follow-up care needs assessment''(pre-discharge), ''immediate, tailored follow-up care''(post-discharge), and ''improved communication between stakeholders''(general). Barriers included ''shortage of hospital beds'' and ''lack of time''(pre-discharge), ''lack of available primary care professionals''(post-discharge), ''inconsistencies of stakeholders' schedules'' and ''intervention costs''(general). Conclusions: The factors identified could serve as a non-exhaustive inventory list to inspire readers who wish to implement a multidisciplinary transitional care intervention in their settings. Digital tools and alternative financing models might overcome cost and reimbursement issues, the increasing complexity of patient care, and shortcomings, such as the lack of available hospital beds or professionals. Further research should identify effective implementation strategies, considering the pre-, post-discharge, and general factors identified. Registration: The protocol was registered in PROSPERO (CRD42023421423). Tweetable abstract: Effective communication aids in implementing transitional care interventions, but patient care complexity and healthcare system pressures present challenges.